El protestantismo de Benito Pérez Galdós = Abweichender Titel: The Protestantism of Benito Pérez Galdós - Sol Rodríguez, Román (Cauriensia, 2025)
In Pérez Galdós's novels it is common to find characters who are priests and, since he is often critical of them, he has been considered by some people to be close to Protestantism. Therefore, we are going to look at the presence of Protestantism in his novels, in protestant characters and also in mentions of Luther; and in the different types of Catholic priests that he offers, with special attention to Nazarín, since it seems that the image of the ideal priest that Galdós could have in mind focuses on him.